Estudo da cinética de recuperação hidrotermal de potássio de siltitos glauconíticos utilizando hidróxido de cálcio - Tomaz, Maria Rita Costa (2020)
Potassium (K) is a macronutrient with enormous importance for plant development, responsible for vital functions such as photosynthesis, transport of sugar and water, and protein synthesis. It is widely used as raw material in the composition of agricultural fertilizer. Brazil depends on fertilizer importation, which reinforces the importance of obtaining K from alternative methods. Development of K-bearing fertilizers from national rocks is important for the country as it would benefit various sectors such as agricultural and minerals. In this sense, extraction of K from a rock found in the midwest of Minas Gerais state, in the vicinity of São Gotardo, appears as an alternative to the traditional KCl fertilizer. Refers to the rock called “Verdete”, a glauconite siltstone composed of quartz, micas and K-feldspar, with K2O content that may vary from 7 to 14%. This work aims to study the kinetics of (RK) K recovery from Verdete in the presence of calcium hydroxide employing a hydrothermal procedure in traditional and rotary autoclaves. Samples were processed at times of 0.25, 0.30, 0.75, 1, 3, 5, 10 and 24 h. Hydrothermal products were characterized by flame photometry, pHmeter and scanning electron microscopy (SEM). The results showed that agitation influenced the behavior of the reaction. At 140 and 180 °C, for low Ca(OH)2 to Verdete ratios (RCV), there was no significant difference in RK comparing procedures conducted with or without agitation. Increasing RCV, it was found that agitation favored RK at 180 °C, but decreased its value when operating at 140 °C. In general, operations at 140 °C provide higher RK for low RCV, while operations at 180 °C gives higher RK for higher RCV. It was also observed that the pH of the reaction solution decreases gradually with time. For procedures without agitation at 100 °C with low RCV values, the reaction rate was found to follow a 1st order kinetics with a rate constant of 0.15 Lsolution gVerdete-1 h-1. In addition, it possible to identify the chemical reaction as the rate-controlling step for agitated and non-agitated procedures. SEM analyses showed that the insoluble fraction of hydrothermal products is composed by tobermorite, while the soluble fraction is composed of calcium carbonate in the forms of aragonite and calcite.